Towards Role Definition in Agile AI-based System Development: Perspectives and Reflections - Souza, Francisco Carlos Monteiro; Souza, Alinne Cristinne Corrêa; Amorim, Bruno Faustino; Cordeiro, Thiago Damasceno (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2024: Anais do XXIII Simpósio Brasileiro de Qualidade de Software, 2024)
With the evolution of AI, software engineering practices must adapt to the unique demands of AI-based systems, ranging from standalone intelligent agents to complex machine learning applications in fields like healthcare and autonomous vehicles. This paper investigates the roles required for AI-based system development from literature and professionals’ perception and how we can integrate these roles with Scrum teams focusing on intelligent agents for multi-agent systems, pattern recognition systems, and evolutionary computation for optimization problems. Initially, a integrative review was conducted, and a survey was applied with 11 AI professionals allocated to different organizations. Our results indicate partial alignment of AI-based system development teams with existing literature regarding roles and responsibilities, highlighting the need for formalized collaborations.